2000
DOI: 10.1006/viro.1999.0169
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interactions of a Potyvirus and a Phloem-Limited Crinivirus in Sweet Potato Plants

Abstract: When infecting alone, Sweet potato feathery mottle virus (SPFMV, genus Potyvirus) and Sweet potato chlorotic stunt virus (SPCSV, genus Crinivirus) cause no or only mild symptoms (slight stunting and purpling), respectively, in the sweet potato (Ipomoea batatas L. ). In the SPFMV-resistant cv. Tanzania, SPFMV is also present at extremely low titers, though plants are systemically infected. However, infection with both viruses results in the development of sweet potato virus disease (SPVD) characterized by sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
167
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(180 citation statements)
references
References 55 publications
7
167
0
3
Order By: Relevance
“…Further, they showed a gradual decline contrary to higher titers (600 fold increase at 5 weeks after inoculation) which should be found in dual and synergistic interactions (Karyeija et al, 2000). This clearly suggests that the synergism was somehow halted in resistant plants since SPCSV was found in lower leaves as expected in single or multiple infections whereas SPFMV was found in all leaf positions but in reduced titers .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Further, they showed a gradual decline contrary to higher titers (600 fold increase at 5 weeks after inoculation) which should be found in dual and synergistic interactions (Karyeija et al, 2000). This clearly suggests that the synergism was somehow halted in resistant plants since SPCSV was found in lower leaves as expected in single or multiple infections whereas SPFMV was found in all leaf positions but in reduced titers .…”
Section: Discussionmentioning
confidence: 82%
“…Shukla et al (1994) observed the same in single infections and argued that serology has low detection limits, at least 1-10 ng of virus per kilogramme of infected tissue. Karyeija et al (2000) and Mukasa et al (2006) also reported that plants that tested negative from ELISA could test positive using sensitive methods like grafting on Ipomoea setosa plants. Reversion was not observed in sweetpotato unlike in cassava as reported by Storey and Nichols (1938) with respect to African cassava mosaic virus disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the perpetuation of these single viruses from one crop to the next means that there is always available inoculum from which dual and synergistic interactions could be reconstituted. Co-infection of SPCSV with SPFMV results in the severe SPVD and during this synergistic interaction the titres of SPFMV are elevated by over 600 folds while the titres of SPCSV remain unchanged (Karyeija et al, 2000a;Mukasa et al, 2006).This implies that, the farmers' practice of selecting healthy-looking vines as the source of planting material would to minimise keep SPFMV inoculums low since farmers would select against SPVD affected vines that harbor high tires of SPFMV. Among the sampled health looking vines only 8.3% were infected by SPVD.…”
Section: Discussionmentioning
confidence: 99%
“…Sweet potato chlorotic stunt virus (SPCSV; genus Crinivirus, family Closteroviridae) is a phloem-limited, whitefly-transmitted, bipartite virus that acts synergistically with several unrelated viruses also infecting sweetpotato (Ipomoea batatas L.) (Gibson et al, 1998;Karyeija et al, 2000;Kokkinos & Clark, 2006;Mukasa et al, 2006;Untiveros et al, 2007). Among the synergistic interactions, co-infection of SPCSV with sweet potato feathery mottle virus (SPFMV; genus Potyvirus, family Potyviridae) causes the severe sweet potato virus disease (SPVD), economically the most devastating disease affecting sweetpotatoes (Milgram et al, 1996; The GenBank/EMBL/DDBJ accession numbers for the sequences of the 39-proximal region of RNA1 are EU124491 (isolate Is), EU124490 (m2-47), EU124493 (Mis1), EU124494 (Tug2) and EU124492 (Unj2), and for Hsp70h sequences are EU124487 (Is), EU124488 (m2-47) and EU124489 (Tug2).…”
Section: Introductionmentioning
confidence: 99%